1989
DOI: 10.1016/0014-4800(89)90019-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a murine model to study the pathogenesis of rotavirus infection

Abstract: A murine model to study enteritis induced by bovine (BRV) and murine rotavirus (MRV) has been developed. The course of infection was determined by clinical symptoms of diarrhea and virus isolation as well as histopathological, immunohistochemical, and electron microscopic methods. Both isolates were able to replicate and produce clinical symptoms in neonatal mice. Rotavirus-free neonates were orally inoculated with MRV or BRV and observed over a 192-hr postinoculation (HPI) period. Following infection with 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Ijaz et al used suckling mice to compare the virulence of bovine RVA (BRV) and murine RVA (MRV) and found that an inoculation dose as low as 100 PFU/mouse of BRV and 10 PFU/mouse of MRV could induce disease in mice (47). In consideration of animal welfare, the 50% lethal dose of MSLH14 was not determined but a preliminary animal test showed that a dose as low as 5 Ď« 10 2 TCID 50 of virus could induce rapid infection of suckling mice with 100% mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Ijaz et al used suckling mice to compare the virulence of bovine RVA (BRV) and murine RVA (MRV) and found that an inoculation dose as low as 100 PFU/mouse of BRV and 10 PFU/mouse of MRV could induce disease in mice (47). In consideration of animal welfare, the 50% lethal dose of MSLH14 was not determined but a preliminary animal test showed that a dose as low as 5 Ď« 10 2 TCID 50 of virus could induce rapid infection of suckling mice with 100% mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The pups were challenged either with BRV C486 or murine RV EC w . Pup challenge conditions for both strains were standardized in order to produce diarrhea in 100% of the nontreated control pups similarly to a previous report (26,36). On day 1, at 2 h after the VHH administration pups received 20 l of 5% bicarbonate solution, they were also challenged by the intragastric route with 100 l of BRV C486 containing a total of 30 times the dose that caused diarrhea in 50% of suckling mice (DD 50 ) (6 Ď« 10 5 FFU/mouse) (experiment A) or with 100 l of murine RV EC w containing 316 DD 50 (experiment B).…”
Section: Rvsmentioning
confidence: 99%
“…Not only homologous rotaviruses such as EW, ER and YR-1, but also heterologous strains such as SA11 (G3), MO (G3) and a vaccine candidate strain (e.g., RRV, G3) cause gastroenteritis in newborn mice (6)(7)(8)(9). The conventional method of serotyping is the plaque-or focus-reduction neutralization assay.…”
Section: E2 or Bc5 (G3) St-2g7 Or Be18 (G4) Yo-is3 Ku-6b11 Or Yo-mentioning
confidence: 99%
“…Passive immune prophylaxis of rotavirus gastroenteritis was proved to be feasible in suckling mice and infants with lyophilized colostral milk from human rotavirus-immunized cows (6). For experiments with active and passive immunity against rotavirus gastroenteritis, a murine model has been employed by using either homologous or heterologous rotaviruses (6)(7)(8)(9). Epizootic diarrhea of newborn mice, YR-1, was observed in Japan in 1974 (10).…”
mentioning
confidence: 99%